Task Petri Nets for Agent Based Computing - Upadhyay, Prajna Devi; Acharya, Sudipta; Dutta, Animesh (INFOCOMP Journal of Computer Science, 2013)
Agent Based Computing is an emerging area of research for the last couple of decades. The agents must be capable of maintaining the inherent dependencies between different tasks or handling resource constraints while working together. There is a need of a formal tool that can represent this autonomous behavior and task delegation property of agents. This paper proposes a new formal tool called Task Petri Nets to represent the collaboration of agents in Multi agent system (MAS). A Task Petri Nets is an extended Petri Nets tool which can represent the autonomous behavior of agents while executing any task maintaining the happened before relationships and handling resource constraints. It can also evaluate the performance of the system using three metrics- Total Execution Time, Agent Utilization and Resource Utilization.